Aggregating factors of the change process in the treatment of anorexia nervosa. (December 2015) - Gumz, Antje; Kästner, Denise; Raczka, Karolina A.; Weigel, Angelika; Osen, Bernhard; Rose, Matthias; Meyer, Björn; Wollburg, Eileen; Voderholzer, Ulrich; Karacic, Matislava; Vettorazzi, Eik; Löwe, Bernd
Abstract: Purpose: We aimed to reduce the large body of factors which may be associated with the change process in treatments for Anorexia Nervosa (AN) into a clinically and scientifically useful number of higher-rank dimensions. In addition, we examined the associations between the identified factors and eating disorder psychopathology and body mass index (BMI) in exploratory analyses. Methods: Within a naturalistic multicenter study we administered the Change Process Questionnaire (CPQ-AN) to inpatients with AN upon admission. The factorial structure of the CPQ-AN was explored via factor analysis. Multiple regression analyses were performed to examine the associations with BMI and eating disorder symptomatology (EDI-2). Results: In total 233 female inpatients with AN (mean BMI = 14.9 kg/m 2, SD = 1.7) participated. The factor analysis yielded four latent factors: basic need satisfaction, AN-specific cognitions and behavior, emotional involvement and commitment to treatment, and alliance and treatment confidence. Furthermore, greater basic need satisfaction and less AN-specific cognitions and behavior predicted lower EDI-2 scores. Higher alliance and treatment confidence were associated with higher BMI as well as a lower EDI-2 score. Conclusion: The associations between the newly derived dimensions and BMI and AN-psychopathology provide evidence to support the clinical relevance of the identified change process dimensions. Future investigations could provide further insights to deepen our understanding of the change process in AN. Highlights: We found higher-rank factors relevant to the change process in AN. The results indicate the clinical relevance of the identified factors. Future analyses using these factors might provide insights into the change process.